Cost-effectiveness of Staple Line Reinforcement in Laparoscopic Sleeve Gastrectomy. Issue 1 (24th January 2023) - Highet, Alexandra; Johnson, Emily H.; Bonham, Aaron J.; Hutton, David W.; Zhou, Shuhao; Thalji, Ameen S.; Ghaferi, Amir A.
Abstract : Objective: To perform a cost-effectiveness analysis of staple-line reinforcement in laparoscopic sleeve gastrectomy. Summary of Background Data: Exponential increases in surgical costs have underscored the critical need for evidence-based methods to determine the relative value of surgical devices. One such device is staple-line reinforcement, thought to decrease bleeding rates in laparoscopic sleeve gastrectomy. Methods: Two intervention arms were modeled, staple-line reinforcement and standard nonreinforced stapling. Bleed and leak rates and 30-day treatment costs were obtained from national and state registries. Quality-adjusted life-year (QALY) values were drawn from previous literature. Device prices were drawn from institutional data. A final incremental cost-effectiveness ratio was calculated, and one-way and probabilistic sensitivity analyses were performed. Results: A total of 346, 530 patient records from 2012 to 2018 were included. Complication rates for the reinforced and standard cohorts were 0.05% for major bleed in both cohorts ( P = 0.8841); 0.45% compared with 0.59% for minor bleed ( P < 0.0001); and 0.24% compared with 0.26% for leak ( P = 0.4812). Median cost for a major bleed was 5552 (3287, 16, 817) and 2406 (1861, 3484) for a minor bleed. Median leak cost was 9897 (4589, 21, 619) and median cost for patients who did not experience a bleed, leak, or other serious complication was 1908 (1712, 2739). Mean incremental cost of reinforced stapling compared with standard was 819.60/surgery. Net QALY gain with reinforced stapling compared with standard was 0.00002. The resultant incremental cost-effectiveness ratio was 40, 553, 000/QALY. One-way and probabilistic sensitivity analyses failed to produce a value below 150, 000/QALY. Conclusions: Compared with standard stapling, reinforced stapling reduces minor postoperative bleeding but not major bleeding or leaks and is not cost-effective if routinely used in laparoscopic sleeve gastrectomy.